Hubungan Personal Hygiene dengan Kejadian Skabies pada Santri Pondok Pesantren X Semarang - Rahmawati, Ana Novia; Hestiningsih, Retno; Wuryanto, M Arie (Jurnal Ilmiah Mahasiswa, 2021)
Scabies is a contagious skin disease caused by Sarcoptes scabiei. In the world, the prevalence of scabies is estimated to be more than 200 million people every year. In Indonesia, scabies ranks 3 of the 12 most common skin diseases. Islamic boarding school students are at risk of contracting scabies. Personal hygiene generally gets less attention from the students. Low personal hygiene is a factor in the development of scabies. This study aimed to analyze the relationship between personal hygiene and scabies incident. This study conducted using quantitative observational study methods with a cross-sectional approach. The sample in this study was 107 Islamic boarding school students. The sampling technique used in this study is purposive sampling. This study uses a questionnaire to determine the variables studied. Data would be analyzed using a chi-square test. The results of this study showed a significant relationship between the cleanliness of clothes (p-value= 0.001). There was no relationship between Cleanliness of skin (p-value=0,857), cleanliness of hand and nail (p-value=0,498), cleanliness of towel (p-value=0,699), cleanliness of bedding (p-value (p-value= 0,966).